2015
DOI: 10.1152/jn.00229.2014
|View full text |Cite
|
Sign up to set email alerts
|

The effect of force feedback delay on stiffness perception and grip force modulation during tool-mediated interaction with elastic force fields

Abstract: During interaction with objects, we form an internal representation of their mechanical properties. This representation is used for perception and for guiding actions, such as in precision grip, where grip force is modulated with the predicted load forces. In this study, we explored the relationship between grip force adjustment and perception of stiffness during interaction with linear elastic force fields. In a forced-choice paradigm, participants probed pairs of virtual force fields while grasping a force s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 58 publications
9
52
5
Order By: Relevance
“…4(a). Consistent with previous studies (Leib, Karniel & Nisky 2015), for the zero tactor displacement gain, this difference was negative; in other words, the participants decreased their grip force as they formed a representation of the force field that they touched. Increasing the tactor displacement gain led to a relative increase in the peak grip force-peak load force ratio.…”
Section: Skin-stretch Caused An Increase In the Applied Grip Forcesupporting
confidence: 89%
See 1 more Smart Citation
“…4(a). Consistent with previous studies (Leib, Karniel & Nisky 2015), for the zero tactor displacement gain, this difference was negative; in other words, the participants decreased their grip force as they formed a representation of the force field that they touched. Increasing the tactor displacement gain led to a relative increase in the peak grip force-peak load force ratio.…”
Section: Skin-stretch Caused An Increase In the Applied Grip Forcesupporting
confidence: 89%
“…In contrast, the introduction of a delay in visual feedback of movement led to a persistent alteration of grip force control that could be accounted by an illusory change in object dynamics (Sarlegna, Baud-Bovy & Danion 2010). Leib et al (Leib, Karniel & Nisky 2015) found that during interactions with linear elastic force fields, a delay in the force feedback produced the illusion of touching a softer elastic force field, but the participants' grip force was predictively adjusted to the correct stiffness level and timing. This dissociation could be specific to the delayed feedback, but it could also be related to differences in the contribution of tactile and kinesthetic information.…”
Section: Introductionmentioning
confidence: 96%
“…If our participants represented time, it only partially contributed to the adaptation and was not transferred to blind reaching and tracking. Similar temporal adjustments were also observed with delayed force feedback (Witney et al 1999; Levy et al 2010; Leib et al 2015; Avraham et al 2017); such adjustments may be based on the capability of sensory organs that respond to force, such as the Golgi tendon organ (Houk and Simon, 1967) or mechanoreceptors in the skin of the fingers (Zimmerman et al 2014), to represent delay as a time lag.…”
Section: Discussionmentioning
confidence: 60%
“…The current literature is equivocal on how delays are represented. Humans can adapt to visuomotor delays (Miall and Jackson, 2006; Botzer and Karniel, 2013) and delayed force feedback (Witney et al 1999; Levy et al 2010; Leib et al 2015; Avraham et al 2017). However, delayed feedback biases perception of impedance (Pressman et al 2007; Nisky et al 2008, 2010; Di Luca et al 2011; Kuling et al 2015; Takamuku and Gomi, 2015; Leib et al 2016), suggesting that the sensorimotor system has limited capability to realign the signals for accurate estimations of the environment (Ionta et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Adaptation to delayed information can be obtained by representing the perturbation as time-based or state-based. On one hand, recent studies provided support for time-based representation of both delayed force field and visual feedback (Witney et al, 1999, Levy et al, 2010, Rohde et al, 2014, Leib et al, 2015, Avraham et al, 2017. In contrast, other studies provided evidences for state-based representation, and that participants were not able to correctly represent the delay as time difference.…”
Section: Adaptation and Representation Of Visuomotor Delaymentioning
confidence: 98%